2017
DOI: 10.4103/sni.sni_56_17
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in fibrinolytic parameters in patients with acute traumatic brain injury

Abstract: Background:Coagulopathy and old age have been associated with poor outcomes in traumatic brain injury (TBI) patients; however, the relationships of coagulopathy and age with the acute phase of TBI remain unclear. We hypothesized that coagulation/fibrinolytic abnormalities are more severe in older patients in the acute phase of TBI and may explain, in part, their poor outcome.Methods:We analyzed the relationship between coagulation/fibrinolytic parameters and age in the acute phase of TBI by retrospectively eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We evaluated 1543 cases with TBI managed from April 2007 to December 2018. Of these, 345, 405, and 523 cases (some of the cases overlap) were from our previous studies published in 2016, 2017, and 2019, respectively [ 7 , 8 , 9 ]. The mechanisms of injury were traffic accidents in 899 patients (58.3%), falls in 564 patients (36.5%), and other mechanisms in 80 patients (5.2%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We evaluated 1543 cases with TBI managed from April 2007 to December 2018. Of these, 345, 405, and 523 cases (some of the cases overlap) were from our previous studies published in 2016, 2017, and 2019, respectively [ 7 , 8 , 9 ]. The mechanisms of injury were traffic accidents in 899 patients (58.3%), falls in 564 patients (36.5%), and other mechanisms in 80 patients (5.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent papers have reported the time-course of coagulation and fibrinolytic variables in TBI in its acute phase [ 7 , 9 , 36 , 37 ]. We reported that the plasma levels of D-dimer on admission were higher in TBI patients with a poor outcome than those with a good outcome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that fibrinolytic activation following TBI is greater in older patients 26 . For this reason, we will examine the effect of tranexamic acid on head injury death stratified by age.…”
Section: Statistical Analysis Planmentioning
confidence: 99%